2008
DOI: 10.1016/j.jjcc.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Valsartan improves l-NAME-exacerbated cardiac fibrosis with TGF-β inhibition and apoptosis induction in spontaneously hypertensive rats

Abstract: This study was designed to investigate whether chronic angiotensin II type 1 receptor blockade inhibits ventricular interstitial fibrosis with the induction of programmed cell death (apoptosis) in prolonged nitric oxide synthase (NOS) inhibition using N(G)-nitro-l-arginine methyl ester (L-NAME) in spontaneously hypertensive rats (SHR). Four groups of 20-week-old male SHR were studied for 3 weeks: the control group; the L-NAME group given 80 mg/L L-NAME in drinking water; and the groups given 1 or 30 mg/(kg day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The caspase is involved in apoptosis, and therefore it was used in the present study as a marker of apoptosis. Previous studies showed that valsartan, an angiotensin II antagonist, could exert an effect on apoptosis and left ventricular remodeling (10,14,15). However, the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The caspase is involved in apoptosis, and therefore it was used in the present study as a marker of apoptosis. Previous studies showed that valsartan, an angiotensin II antagonist, could exert an effect on apoptosis and left ventricular remodeling (10,14,15). However, the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we proved that Candesartan significantly delayed the process of EMT by decreasing the expression of collagens and fibronectins. Plenty of studies suggested that excessive accumulation of newly formed ECM could be suppressed by ARBs in heart, lung, liver and kidney (Akashiba et al, 2008;Sukumaran et al, 2010), and the attenuated MMP activities might be the underlying mechanism, which was different from the various of ECM signaling molecules, such as Smads and PKC. Here we found that Smad7 upregulation was required for Candesartan induced MMP-9 suppression in pressure overload hearts.…”
Section: Discussionmentioning
confidence: 99%
“…The ARB, valsartan reduced the degree of myocardial fibrosis in hypertensive rats [43]. Similarly, candesartan, which is another ARB, reduced interstitial fibrosis and AF duration in a canine model of AF [44].…”
Section: Introductionmentioning
confidence: 99%